Development and implementation of an interactive muti-modality (IMM) for self-management support among patients with type 2 diabetes in Bangkok, Thailand - Suwaree Wongrochananan (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2011